2019
DOI: 10.7554/elife.47788
|View full text |Cite
|
Sign up to set email alerts
|

A single clonal lineage of transmissible cancer identified in two marine mussel species in South America and Europe

Abstract: Transmissible cancers, in which cancer cells themselves act as an infectious agent, have been identified in Tasmanian devils, dogs, and four bivalves. We investigated a disseminated neoplasia affecting geographically distant populations of two species of mussels (Mytilus chilensis in South America and M. edulis in Europe). Sequencing alleles from four loci (two nuclear and two mitochondrial) provided evidence of transmissible cancer in both species. Phylogenetic analysis of cancer-associated alleles and analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
270
3

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(282 citation statements)
references
References 50 publications
9
270
3
Order By: Relevance
“…So far, horizontally transmitted cancers have been identified in very few species in the wild, namely in dog (canine transmissible venereal tumour), in Tasmanian devil (devil facial tumour diseases), and in four bivalve species (clam leukaemia) (Ujvari et al, 2016b). In each case, phylogenetic analyses revealed that few monophyletic lines of transmissible cancerous cells widely spread in populations (Murgia et al, 2006; Pye et al, 2016; Baez-Ortega et al, 2019; Yonemitsu et al, 2019), suggesting low rates of neoplasia and high transmission rates. In two of the three cases, infection by contemporary transmissible cancers is highly virulent (in bivalve and Tasmanian devil; Barber, 2004; Lachish et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…So far, horizontally transmitted cancers have been identified in very few species in the wild, namely in dog (canine transmissible venereal tumour), in Tasmanian devil (devil facial tumour diseases), and in four bivalve species (clam leukaemia) (Ujvari et al, 2016b). In each case, phylogenetic analyses revealed that few monophyletic lines of transmissible cancerous cells widely spread in populations (Murgia et al, 2006; Pye et al, 2016; Baez-Ortega et al, 2019; Yonemitsu et al, 2019), suggesting low rates of neoplasia and high transmission rates. In two of the three cases, infection by contemporary transmissible cancers is highly virulent (in bivalve and Tasmanian devil; Barber, 2004; Lachish et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Transmissible cancers are directly transmitted to new hosts, and do not require cells or viral particles of another taxon to play any role in the infection system. So far, transmissible cancerous cell lines have been observed in a few taxa only, namely three mammal species (Ashbel, 1945; Murgia et al, 2006; Murchison, 2008; Pye et al, 2016) and four bivalve species (Metzger et al, 2015, 2016; Yonemitsu et al, 2019), but early multicellular organisms, with presumably basic anticancer defenses, may have been plagued by this problem more than extant ones (as argued by Ujvari et al, 2016b; Thomas et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Such neoplastic cells may be propagated from one individual and transmitted to others through sea water . In recent, the group of Metzger elucidated how the cancer cells of mussels were transferred across the Atlantic and Pacific Oceans and between the Northern and Southern hemispheres . By knowing this situation, we will have more interest in how the cancer cells transfer into the mussels in the Asian area.…”
Section: Discussionmentioning
confidence: 99%
“…Understanding the interaction between infectious cancers and the host immune system is key to developing effective disease management strategies. (Pearse & Swift, 2006;Pye, Pemberton, et al, 2016) and six lineages of transmissible neoplasia circulating in six species of marine bivalves Yonemitsu et al, 2019). In CTVT and DFTD, immune evasion is at least partially achieved through downregulation of the major histocompatibility complex (MHC) proteins from the tumour cells' surface (Siddle et al, 2013;Yang, Chandler, & Dunne-Anway, 1987).…”
Section: Immune Re S P On S E S To Infec Ti Ous C An Cer S In Wildlifementioning
confidence: 99%